Review of Rice Cultivation in Chhattisgarh - Priti Sandeep Bhandarkar,; Sandeep Bhandarkar, (Public Health, 2026)
Rice is the most important staple crop of Chhattisgarh and constitutes the backbone of the state’s agricultural economy and rural livelihoods. The state cultivates rice on approximately 3.77–3.80 million hectares, representing nearly 70% of the total cropped area. Although productivity historically remained below the national average due to the predominance of rainfed ecosystems, substantial improvement has been observed during the past two decades. Research and extension initiatives undertaken by Indira Gandhi Krishi Vishwavidyalaya have significantly contributed to germplasm conservation, varietal improvement and crop production technologies. The adoption of improved varieties, hybrid rice, balanced nutrient management and increasing seed replacement rates have enhanced rice productivity. Supportive government policies including minimum support price and efficient procurement mechanisms have further strengthened farmer participation in rice-based production systems. Recent procurement exceeding 14 million tonnes of paddy reflects the growing stability of rice production in the state. This review synthesizes information on agro-climatic conditions, varietal diversity, seed systems, productivity trends and policy interventions influencing rice cultivation in Chhattisgarh and highlights major constraints and future research priorities for sustainable rice production.